Atorvastatin induces autophagy in MDA-MB-231 breast cancer cells. (3rd September 2018) - Hu, Ming-Bai; Zhang, Jing-Wei; Gao, Jing-Bo; Qi, Yu-Wen; Gao, Yang; Xu, Liu; Ma, Yanbing; Wei, Zheng-Zhuan
ABSTRACT: This article explores the effects of atorvastatin on cultured breast cancer cells. Our experiment demonstrated that atorvastatin triggered autophagy and inhibited proliferation in breast cancer cells. A CCK8 assay indicated that atorvastatin can inhibit the activity of MDA-MB-231 breast cancer cells. Western blotting results showed that atorvastatin increased the conversion of light chain 3 (LC3)-I to LC3-phosphatidylethanolamine conjugate (LC3-II). Confocal microscopy was used to reveal the appearance of a punctate structure in the cytoplasm, and electron microscopy was used to reveal the formation of double-membrane autophagosome. In conclusion, our study showed that atorvastatin may affect MDA-MB-231 breast cancer cells by inducing autophagy.